2016
DOI: 10.4238/gmr.15038583
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum HGF and CK18 levels in patients with esophageal cancer

Abstract: ABSTRACT. Cytokeratins are thought to play a role in apoptosis. Cytokeratin 18 (CK18) is involved in the formation of intracellular cytoskeleton, and has been considered a promising apoptosis marker in gastrointestinal carcinomas. Growth factors, including hepatocyte growth factor (HGF), may provide a microenvironment for malignant cells. In this study, we aimed to compare serum HGF and CK18 levels between esophageal squamous cell carcinoma patients and healthy controls. The study included 41 adult patients (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Patients with relatively lower level of total and caspase cleaved CK18 were predicted to have better prognosis. This observation is consistent with reports from other types of cancers, including breast cancer, lung cancer and esophageal cancer [31,33,34]. However, results from immunohistochemistry staining of CK18 in breast cancer samples manifested reverse results [33].…”
Section: Discussionsupporting
confidence: 91%
“…Patients with relatively lower level of total and caspase cleaved CK18 were predicted to have better prognosis. This observation is consistent with reports from other types of cancers, including breast cancer, lung cancer and esophageal cancer [31,33,34]. However, results from immunohistochemistry staining of CK18 in breast cancer samples manifested reverse results [33].…”
Section: Discussionsupporting
confidence: 91%
“…KRT18 is a type I intermediate filament protein that extends from the surface of the nucleus to the cell membrane, and involved in a variety of cellular processes including cell proliferation, cell cycle, apoptosis, motility, and cell signaling [14]. In recent decade, KRT18 was suggested to be up-regulated in various human tumor tissues including lung cancer [15], invasive breast cancer [16], esophageal cancer [17], gastric cancer [18], hepatocellular carcinoma [19], bladder cancer [20], ovarian cancer [21], oral squamous cell carcinoma [22], pancreatic cancer [23], prostate cancer [24], and so on. Drew et al [12]performed multivariate discriminant analysis on the hCellMarkerPlex gene expression data including human colon normal tissues, colon adenomatous polyp tissues and colon carcinoma tissues, and found that colon normal tissues had significantly low KRT18 expression compared with colon adenomatous polyp tissues and colon carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Higher serum levels of HGF also showed significant correlation with the stage of disease and survival [216]. Similarly, in another study, increased serum levels of HGF were found to be correlated with tumor stage (p ¼ .002) and metastasis (p < .001) [217]. Conversely, conflicting results emerged from a study concerning the prognostic value of HGF in esophageal squamous cell carcinoma patients.…”
Section: V-d-esophageal Cancermentioning
confidence: 96%